Late colonic recurrence of endometrial adenocarcinoma - Suárez-Torres, Ismael (2017)
The recurrence rate of endometrial carcinoma after surgery plus radiotherapy is low and, in most cases, it occurs within the first 3 years of treatment. The vaginal vault is the most common site of recurrence. Recurrence of endometrial cancer to the colon is very rare. We report a 69-year-old woman who presented with right iliac fossa pain, anorexia and weight loss for five months. She had a history of total abdominal hysterectomy and bilateral oophorosalpingectomy for stage IA endometrial carcinoma 7 years ago. Colonoscopy revealed a mid-sigmoid colon stricture suspicious of external compression. A CT scan did not reveal if the tumor was arising from the sigmoid colon or abutting it. During laparotomy, we found macroscopic disease involving transverse colon and small bowel mesentery with an ischemic stricture was found. Bowel resection and total omentectomy were performed leaving no residual macroscopic disease. Immunohistochemistry analysis revealed a poorly-differentiated endometrial adenocarcinoma. Patient recovered without complications and was treated with chemotherapy.